Student Knowledge About Sleep Paralysis - Rahayu, Sri Mulyati; Marlina, Yani; Ulfah, Diana (Formosa Journal of Sustainable Research, 2024)
Sleep paralysis (SP) is a sleep disorder characterized by the inability to move when awakened from sleep and the appearance of hallucinations, such as seeing shadows or hearing voices. Sleep paralysis occurs due to stress, physical fatigue, anxiety, and poor sleep quality. This condition has an impact on reduced concentration, motivation, health conditions, and decreased completion of tasks. The aim of the research is to determine students' knowledge about sleep paralysis. The research method was descriptive, with a population of D III nursing students with a sample size of 83 students. The results are that almost half of the respondents have insufficient knowledge. Conclusion: Sleep paralysis is not the result of the presence of supernatural beings, but rather a condition of paralysis, especially sensory movement muscles, which occurs during sleep and is a normal thing, so recommendations need to be provided with education about efforts to prevent sleep paralysis